A meta-analysis of leadership and workplace safety: Examining relative importance, contextual contingencies, and methodological moderators. - Lyubykh, Zhanna; Turner, Nick; Hershcovis, M. Sandy; Deng, Connie (Journal of Applied Psychology, 2022)
= 104,364), we find that although leadership behaviors are associated with workplace safety, the leadership categories vary considerably in their relative importance. Task-oriented leadership followed by relational-oriented leadership emerge as the most important contributors to workplace safety. Change-oriented leadership (which includes transformational leadership) does not emerge as the largest contributor for any of the seven tested safety variables, despite it being the most frequently examined leadership model in the workplace safety literature. Effectiveness of leadership behaviors in relation to workplace safety varies by national culture power distance, industry risk, workforce age, as well as by contextualized forms of leadership (i.e., safety-specific vs. generalized). Finally, there is meta-analytic evidence for publication bias and common-method variance. (PsycInfo Database Record (c) 2022 APA, all rights reserved).